PERILAKU RUNTUH BALOK BETON BERTULANG YANG DIPERKUAT DENGAN LAPIS GLASS FIBRE REINFORCED POLYMER (GFRP) - Sudarsana, I Ketut; Rai Widiarsa, Ida Bagus (Jurnal Ilmiah Teknik Sipil; Vol. 12, No. 1 Januari 2008)
This research was conducted to know the failure behavior and flexural strength of reinforced concrete (R/C) beam strengthened with GFRP sheet. The research used simple supported beams with dimension of 100x150x1100 mm. The beam resisted two concentrated loads at a distance of 300 mm from each support. On the beams were applied 3 conditions that were beam without addition of GFRP sheet; beam with addition of 1 layer GFRP sheet and beam with addition of 2 layers GFRP sheet. The GFRP sheets used in this research were made of woven roving glass fibre mixed with epoxy resin. The data collected in this research were crack load, ultimate load, crack pattern, crack width, deflection and failure behavior. Results of from this research indicated that addition of GFRP sheet decreased the length and width of the R/C beam crack. The addition of GFRP sheet improved flexural strength of R/C beam as well. The addition of 1 layer GFRP sheet increased the flexural strength by 10,8 %, with failure in flexure accompanied by breaking of the sheet. On the other hand, the addition of 2 layers GFRP sheet increased the flexural strength by 13,4 %, with failure in flexure accompanied by debonding of the sheet from concrete surface. This showed that the sheet did not work effectively.
Keywords: perilaku runtuh, kuat lentur, balok beton bertulang, lapis GFRP